2020
DOI: 10.3390/ijms21186740
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Cannabidiol, a Non-Intoxicating Compound of Cannabis, on the Cardiovascular System in Health and Disease

Abstract: Cannabidiol (CBD) is a non-intoxicating and generally well-tolerated constituent of cannabis which exhibits potential beneficial properties in a wide range of diseases, including cardiovascular disorders. Due to its complex mechanism of action, CBD may affect the cardiovascular system in different ways. Thus, we reviewed the influence of CBD on this system in health and disease to determine the potential risk of cardiovascular side effects during CBD use for medical and wellness purposes and to elucidate its t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
70
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(91 citation statements)
references
References 160 publications
(508 reference statements)
1
70
0
1
Order By: Relevance
“…Intriguingly, brain hypoxemia, often silent, occurs also with COVID-19, potentially inducing long lasting sequelae even after remission. Furthermore, CBD mitigates in vivo widely differing forms of cardiomyopathies as has been shown in various animal models including ischemia/reperfusion arrhythmias, myocardial infarction, autoimmune myocarditis or diabetic cardiomyopathy (reviewed recently by [34,35]). This includes also a mouse model of doxorubicin-induced cardiotoxicity [36].…”
Section: Cbd Reduces Neuroinflammationmentioning
confidence: 94%
“…Intriguingly, brain hypoxemia, often silent, occurs also with COVID-19, potentially inducing long lasting sequelae even after remission. Furthermore, CBD mitigates in vivo widely differing forms of cardiomyopathies as has been shown in various animal models including ischemia/reperfusion arrhythmias, myocardial infarction, autoimmune myocarditis or diabetic cardiomyopathy (reviewed recently by [34,35]). This includes also a mouse model of doxorubicin-induced cardiotoxicity [36].…”
Section: Cbd Reduces Neuroinflammationmentioning
confidence: 94%
“…Numerous studies have demonstrated a range of beneficial properties associated with CBD, including anti-inflammatory, antioxidant, antiarthritic, cardio- and neuroprotective, anticonvulsant, procognitive and analgesic effects (for detail, see reviews, for example, [ 51 , 52 , 53 ]). At the moment, there are two indications.…”
Section: Cannabidiol—pharmacological Potential and Mechanism Of Acmentioning
confidence: 99%
“…One should also consider that vaping CBD was associated with severe COVID-19 problems [ 57 ] and not overlook the unclear impact of “over-the-counter” CBD on the immunity of the SARS-CoV-2 infection [ 62 ]. Due to the lack of rigorous legal regulations, CBD is indeed commonly used as over-the-counter product, often of unapproved and unknown composition [ 51 , 54 , 55 ].…”
Section: Cannabidiol—pharmacological Potential and Mechanism Of Acmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, CBD acts as an agonist at the following receptors: transient receptor potential ankyrin subfamily member 1 (TRPA1) and vanilloid subfamily members 1–4 (TRPV1–4), peroxisome proliferator-activated receptor γ (PPARγ), orphan G-protein coupled receptors GPR55 and GPR18, and serotonin 5-HT 1A and 5-HT 2A receptors (partial agonist). Moreover, CBD is a positive allosteric modulator of α1-, α1β- and α3-glycine receptors (α1-, α1β- and α3-GlyR), μ- and δ-opioid receptors (μ- and δ-OR) and γ-aminobutyric acid receptor type A (GABA A ) [ 29 ]. Regarding stroke, Hayakawa et al have shown in a series of studies using a mouse model of MCAO that CBD administration reduced infarct size, possibly through 5-HT1A receptor and other mechanisms [ 30 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%